ANALISIS STABILISASI TANAH LEMPUNG MENGGUNAKAN CAMPURAN ABU SEKAM PADI TERHADAP NILAI KUAT GESER TANAH - iwan ristanto, Iwan Ristanto; Adiyanwar Shidiq, Rizhal; Aski Safarizki, Hendramawat (Inisiasi, 2024)
The main aim of stabilization is to change the technical properties of the soil itself, such as the compressibility and bearing capacity of the soil. Based on the results of testing the physical and mechanical properties of the original soil of Sambirejo Village, Puhpelem, Wonogiri according to the ASSHTO method, the original soil is included in group A-7-6, which is medium to poor clayey soil material. Meanwhile, according to the USCS method, it is included in the CH group, namely organic clay with high plasticity, fat clays. After conducting further research with variations in the rice husk ash mixture of 0%, 5%, 10%, 15%, and 20%, the results showed that the soil physical test showed the values of water content (W), liquid limit (LL), plasticity index (PI ), and the percentage passing filter No. 200 experienced a decrease with increasing percentage of addition of rice husk ash with yield figures on original soil of 53.00%, 52.00%, 15.32%, 62.00% while on original soil with a mixture of 20% rice husk ash obtained results of 50.11%, 41.10%, 1.65%, 51.00 %. Meanwhile, the specific gravity (Gs), plasticity limit (PL), and shrinkage limit (LL) increased with increasing percentage of rice husk ash addition with the yield figures on the original soil being 5.409%, 36.68%, 12.65%, while on the original soil with a mixture of rice husk ash 20% rice obtained yields of 6.071%, 39.45%, 26.89%. Based on the results of the Direct Shear Test, the soil experienced an increase with each addition of rice husk ash. The highest Direct Shear Test value occurred in 20% mixed soil, namely 0.583 kg/cm2 and the lowest Direct Shear Test value occurred in original soil, namely 0.394 kg/cm2.